Stapled haemmorhoidopexy versus open haemorrhoidectomy: our initial experience - Ahmad, Mir Mujtaba; Nadeem, Raja; Husain, Musharraf; Nazir, Irfan; Ahmad, Manzoor (International Surgery Journal, 2017)
Background: Haemorrhoids or ‘Piles’ is a frequently observed disease in surgical practice. Various non-surgical and surgical treatments are available. Open haemorrhoidectomy (Milligan-Morgan) is a widely-used procedure. A recent novel technique called ‘Stapled haemorrhoidopexy’, first described and performed by Italian surgeon Antonio Longo is gaining worldwide recognition for its benefits. Methods: A total of 155 patients between the age group of 20 and 65 years, diagnosed to have grade III or IV haemorrhoids were included in the study, divided into 2 groups, Group 1 undergoing Open haemorrhoidectomy (30 patients) and Group 2 undergoing Stapled haemorrhoidectomy (25 patients). Post operatively patients of both groups were reviewed at the time of discharge, at 7 days after discharge, at 1 month and 3 months post-surgery. The significant difference of the percentages between the two groups was tested using the Chi Square test. The significant difference in the mean values between the 2 groups was tested using the Student’s t- independent test. For all the tests, level of significance was taken as 0.05. Results: In present study, the mean operating time for stapled haemorrhoidopexy was 34.96±7.38 minutes with an average of 20-50 minutes, while with open haemorrhoidectomy, the mean operating time was 44.67±11.83 minutes (p<0.001). The mean VAS scores at 6, 12 and 24 hours with stapled haemorrhoidopexy were 1.79±0.76; 1.83±0.61 and 1.47±0.66, respectively, and with open haemorrhoidectomy, the mean VAS scores at 6, 12 and 24 hours were 2.88±0.88; 2.13±0.82 and 1.91±0.83, respectively. The mean hospital stay for patients with stapled haemorrhoidopexy was 1.96±0.55 days in comparison to the open group where the mean hospital stay was 3.51±0.72 days (P-value<0.001). The time for resumption to routine work was shorter in stapled group 8.61±2.76 as compared to 15.34± 2.12 which was statistically significant (P value <0.001). The mean amount of blood loss during stapled hemorrhoidectomy was statistically less than in open surgery. Conclusions:Stapled Haemorrhoidectomy is less painful with shorter duration of hospital stay and resumption of daily activity is faster than the open haemorrhoidectomy. However, long term follow-up is required to know the recurrence rate in stapled haemorrhoidectomy.